Korelasi Pencegahan Bullying Terhadap Motivasi Belajar Bagi Anak Sekolah Dasar 212 Harapan Kota Bandung - Jihan Fikriyyah; Kholizah Fitri Yansyah; Ammara Syahira; Alexandra Panduanisa Patty; Maulia Depriya Kembara (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Bullying behaviour is a delinquency and negative behavioural deviation that is detrimental and has an impact on social relationships, especially for the victims of bullying themselves. It is undeniable that this behaviour can occur at any age and in any social status. This phenomenon is also often found among elementary school children who are very vulnerable to the formation of children's character. Because this age is the foundation of character that will continue to stick until the child grows up. One of the most immediate impacts is losing motivation to learn. This article discusses the relationship between the prevention of bullying behaviour and primary school children's learning motivation. The method we used was qualitative by processing literature review data and conducting observations that implement directly to children in elementary schools regarding bullying prevention and learning motivation for them. Field facts show that the prevention of bullying behaviour on student learning motivation carried out at SDN 212 Harapan Bandung City has a very strong impact on students there and students are aware that bullying behaviour can affect learning motivation for their friends. Students who experience bullying, their level of learning motivation can decrease and even lose interest in learning, and lose confidence in their abilities due to lack of confidence in their academic knowledge ability to feel insecure in social environments and experience considerable mental stress.